Effect of Sm content on activation capability and hydrogen storage performances of TiFe alloy. (13th July 2021) - Zhang, Yanghuan; Shang, Hongwei; Gao, Jinliang; Zhang, Wei; Wei, Xin; Yuan, Zeming
Abstract: Element substitution is an efficient method to enhance the activation property of TiFe alloys. In this paper, Zr, Mn and Ni were utilized to replace Fe in the alloy partially, and different content rare earth Sm substitute Ti in the alloy. The alloys with nominal compositions of Ti1.1- x Fe0.6 Ni0.1 Zr0.1 Mn0.2 Sm x ( x = 0–0.08) were made through vacuum induction melting. The microstructure, composition and hydrogen storage property of alloys were measured in detail by X-ray diffraction, scanning electron microscope, high-resolution transmission electron microscopy and automatically Sievert apparatus. The results reveal that the as-cast alloys contain TiFe as major phase and Ti2 Fe as secondary phase. Sm addition refines the grain of alloys obviously. All alloys have good activation properties and can be completely activated without any heat treatment. The activation performance can be further improved by partially replacing Ti with Sm, and the incubation period of activation can be shortened greatly. Highlights: Sm addition refines the grains of TiFe-based alloys. The activation property of alloys can be improved obviously after adding Sm. Introducing Sm improves the hydrogen storage kinetics of samples. The hydrogen absorption and desorption hysteresis reduces after adding Sm.